Metabolic effect of AOS-iron in rats with iron deficiency anemia using LC-MS/MS based metabolomics - He, Hong; An, Fengping; Huang, Qun; Kong, Yuting; He, Dan; Chen, Lei; Song, Hongbo (Food research international, 2020)
[Display omitted] •Twenty-two metabolites were identified as potential biomarkers by LC-MS/MS metabolomics.•The metabolic pathway of IDA in rats is clarified.•AOS-iron restored the major metabolites in relevant pathway disrupted by IDA to normal. Iron deficiency anemia (IDA) is a worldwide nutritional problem. The metabolic mechanism of IDA is still unclear. So, the underlying metabolic mechanism of iron supplementation has not been reported even if various iron supplements to treat IDA have been studied. The present study aimed to investigate the metabolic mechanisms of IDA and agar oligosaccharide-iron complex (AOS-iron) supplementation in IDA rats by assessing the changes of endogenous metabolites in serum and liver using LC-MS/MS metabolomics approach. Orthogonal partial least-squares discriminant analysis (OPLS-DA) score plots showed significant separation of metabolites in serum and liver among the normal, anemia model and AOS-iron groups. Seventeen and eight metabolites were identified from serum and liver, respectively. Pathway enrichment analysis suggested that potential biomarkers were strongly involved in the biosynthesis of saturated and unsaturated fatty acids, sphingolipid metabolism, glycerophospholipid metabolism, linoleic acid metabolism, Fcγ receptor (FcγR)-mediated phagocytosis, pancreatic cancer metabolism, regulation of autophagy, gonadotropin releasing hormone (GnRH) signaling pathway, fatty acid metabolism, pantothenate and CoA biosynthesis, glutathione metabolism and primary bile acid biosynthesis. After supplementing 2 mg Fe/kg·bw AOS-iron for 4 weeks, the major metabolites in related pathways disrupted by IDA were restored to normal levels. Therefore, AOS-iron effectively treated IDA by regulating metabolic disorders.